Effect of Mulches and Nutrient Levels on Soil Hydro-thermal Regimes, Soil Fertility and Productivity of Cauliflower (Brassica oleracea var. botrytis L.) in Mid-hills of Himachal Pradesh - and Vijay Kumar, J.C. Sharma (Journal of the Indian Society of Soil Science, 2014)
Field experiments were conducted during 2009-10 and 2010-11 to study the effect of mulches and nutrient levels on soil hydro-thermal regimes, soil fertility and productivity of cauliflower (Brassica oleracea var. botrytis L.) in mid-hills of Himachal Pradesh. Twelve treatment combinations comprising four types of mulches viz., black plastic mulch (BP), grass mulch (GM), pine needles mulch (PN), unmulched control (UM) and three levels of nutrients i.e. F1 (125% of recommended dose of NPK), F2 (100% recommended dose of NPK) and F3 (75% of recommended dose of NPK) were replicated thrice in a randomized block design (factorial) in plots of size 3.0 m Ã— 2.5 m and spacing of 60 cm Ã— 45 cm. Results revealed that all mulches maintained comparatively higher soil moisture contents over unmulched control. Among mulches, BP conserved highest moisture which was 39.6-47.0 and 45.3-47.4% greater over UM in 0-7.5 and 0-15 cm soil depths, respectively. Other mulches also conserved higher moisture over UM and followed the order: BP > PN > GM > UM. Mulches favorably moderated soil temperature and BP mulch elevated soil temperature at 7.5 and 15 cm depths and effectiveness of mulches in moderating temperature followed the order: BP > PN > GM > UM at 7:30 hrs and BP > UM > GM > PN at 14:30 hrs. Mulching along with different levels of NPK improved the soil fertility by increasing availability of N, P, K, Ca and SO42–S over unmulched control. The productivity of cauliflower under mulches increased by 16.0-34.6 per cent over unmulched control. Black plastic mulch in combination with 125% of recommended dose of NPK (BPF1) obtained higher curd yield (26.7 t ha-1) as compared to other treatment combinations and showed an increase of 88.7 per cent over unmulched control with 75% of recommended dose of NPK (UMF3).